ANALISIS DAN DESAIN RANTAI PASOK KAKAO BERBASIS BLOCKCHAIN - Dian Ardifah Iswari; Yandra Arkeman; Muslich Muslich (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2019)
The supply chain in the 4.0 era wanted consumers to be closer to producers. Problems that occur in the supply chain are supply chain information flow is still long, there is no transparency, marketing coverage is less extensive, and documentation of activities is not good. The purpose of this study is to analyze the condition of the Kelompok Tani X cocoa supply chain and to identify the attributes of the blockchain based group cocoa supply chain farmers. The method used is the System Development Life Cycle (SDLC). The results obtained are that the supply chain information flow in the X farmer group is still overlapping, and has not been systematic. Actors consist of farmers, farmer leaders, processing factories (Kelompok Tani X), and retailers. Activities that occur are signing up, logging in, filling content, transactions, shipping, validation, and returning goods.